Banana-like appearance of rib fibrous dysplasia in bone scintigraphy and single-photon emission computed tomography (SPECT) - Abdul Halim, Nor Hasniza; Ibrahim, Idris; Mohamed Tarmizi, Nadia; Zakaria, Mohd Hazeman (Wolters Kluwer Medknow Publications, 2025)
The patient, a 37-year-old male, initially presented with per rectal bleed. Colonoscopy revealed a circumferential lesion within the lower rectum, along with a few satellite lesions. At that time, we performed a biopsy, but the histopathological examination revealed consistent solitary rectal ulcer syndrome. Subsequent bone scan revealed increased radiotracer uptake at the left 6 th rib, resulting in a 'banana-like appearance' and a ground glass appearance on the corresponding single-photon emission computed tomography (SPECT), in keeping with fibrous dysplasia. Given his asymptomatic state, the patient received reassurance and surveillance regarding his benign bone lesion.